Aire mediates thymic expression and tolerance of pancreatic antigens via an unconventional transcriptional mechanism. Issue 1 (6th December 2012) - Danso‐Abeam, Dina; Staats, Kim A; Franckaert, Dean; Van Den Bosch, Ludo; Liston, Adrian; Gray, Daniel H D; Dooley, James
<x xml:space="preserve">Abstract</x> The autoimmune regulator (Aire), mediates central tolerance of peripheral self. Its activity in thymic epithelial cells (TECs) directs the ectopic expression of thousands of tissue‐restricted antigens (TRAs), causing the deletion of autoreactive thymocytes. The molecular mechanisms orchestrating the breadth of transcriptional regulation byAire remain unknown. One prominent model capable of explaining both the uniquely high number ofAire‐dependent targets and their specificity posits that tissue‐specific transcription factors induced byAire directly activate their canonical targets, exponentially adding to the total number ofAire‐dependentTRAs. To test this "HierarchicalTranscription" model, we analysed mice deficient in the pancreatic master transcription factor pancreatic and duodenal homeobox 1 (Pdx1), specifically inTECs (Pdx1ΔFoxn1), for the expression and tolerance of pancreaticTRAs. Surprisingly, we found that lack ofPdx1 inTECs did not reduce the transcription of insulin or somatostatin, or alter glucagon expression. Moreover, in a model of thymic deletion driven by a neo‐TRA under the control of the insulin promoter, Pdx1 inTECs was not required to affect thymocyte deletion or the generation of regulatoryT (Treg) cells. These findings suggest that the capacity ofAire to regulate expression of a huge array ofTRAs relies solely on an unconventional transcriptional mechanism, without intermediary transcription factors.